WTD Attenuating Rheumatoid Arthritis via Suppressing Angiogenesis and Modulating the PI3K/AKT/mTOR/HIF-1α Pathway - Ba, Xin; Huang, Ying; Shen, Pan; Huang, Yao; Wang, Hui; Han, Liang; Lin, Wei Ji; Yan, Hui Jia; Xu, Li Jun; Qin, Kai; Chen, Zhe; Tu, Sheng Hao (Frontiers in Pharmacology, 2021)
Background: Wutou Decoction (WTD), as a classic prescription, has been generally used to treat rheumatoid arthritis (RA) for two thousand years in China. However, the potential protective effects of WTD on rheumatoid arthritis and its possible mechanism have rarely been reported. Purpose: The aim of this study was to explore the possible mechanism of WTD against RA and a promising alternative candidate for RA therapy. Methods: A model of collagen-induced arthritis (CIA) was constructed in rats to assess the therapeutic effects of WTD. Histopathological staining, immunofluorescence, and western blotting of synovial sections were conducted to detect the antiangiogenic effects of WTD. Then, cell viability assays, flow cytometry, scratch healing assays, and invasion assays were conducted to explore the effects of WTD on MH7A human fibroblast-like synoviocyte (FLS) cell proliferation, apoptosis, migration, and invasion in vitro. The ability of WTD to induce blood vessel formation after MH7A cell and human umbilical vein endothelial cell line (HUVEC) coculture with WTD intervention was detected by a tube formation assay. The mechanisms of WTD were screened by network pharmacology and confirmed by in vivo and in vitro experiments. Results: WTD ameliorated the symptoms and synovial pannus hyperplasia of CIA rats. Treatment with WTD inhibited MH7A cell proliferation, migration, and invasion and promoted MH7A apoptosis. WTD could inhibit MH7A cell expression of proangiogenic factors, including VEGF and ANGI, to induce HUVEC tube formation. Furthermore, the PI3K-AKT-mTOR-HIF-1α pathway was enriched as a potential target of WTD for the treatment of RA through network pharmacology enrichment analysis. Finally, it was confirmed in vitro and in vivo that WTD inhibits angiogenesis in RA by interrupting the PI3K-AKT-mTOR-HIF-1α pathway. Conclusion: WTD can inhibit synovial hyperplasia and angiogenesis, presumably by inhibiting the migration and invasion of MH7A cells and blocking the production of proangiogenic effectors in MH7A cells. The possible underlying mechanism by which WTD ameliorates angiogenesis in RA is the PI3K-AKT-mTOR-HIF-1α pathway.